Using hypermedia annotations to teach vocabulary on the Web - Bahman Gorjian (Association for Learning Technology, 2011)
This project measured the effect of using hypermedia annotations on short and long-term vocabulary retention in teaching vocabulary through Web-based language learning activities. A total of 62 university students were randomly assigned into two homogeneous groups; and then both groups were given a pretest. Both groups covered 12 expository passages selected by the researchers from the BBC website. The subjects had to sit for an immediate quiz to measure the short-term effect of the treatment and finally, at the end of the course and a twoweek interval, subjects sat for their post-test. Findings revealed that there was a significant effect of the hypermedia annotations on the retention of vocabulary in the short term ( p<0.05). However, the post-test results indicated that the effect of the treatment in the long term faded away, and the significance of the means was not sufficiently high to reject the null hypothesis.